Legume-grass mixtures increase forage yield by improving soil quality in different ecological regions of the Qinghai-Tibet Plateau - Luo, Feng; Liu, Wenhui; Mi, Wenbo; Ma, Xiang; Liu, KaiQiang; Ju, Zeliang; Li, Wen (Frontiers in Plant Science, 2023)
Information on the relationship between soil quality and forage yield of legume-grass mixtures in different ecological regions can guide decision-making to achieve eco-friendly and sustainable pasture production. This study’s objective was to assess the effects of different cropping systems on soil physical properties, nitrogen fractions, enzyme activities, and forage yield and determine suitable legume-grass mixtures for different ecoregions. Oats (Avena sativa L.), forage peas (Pisum sativum L.), common vetch (Vicia sativa L.), and fava beans (Vicia faba L.) were grown in monocultures and mixtures (YS: oats and forage peas; YJ: oats and common vetch; YC: oats and fava beans) in three ecological regions (HZ, GN, MY) in a split-plot design. The results showed that the forage yield decreased with increasing altitude, with an order of GN < HZ < MY. Meanwhile, the forage yield was higher for mixed crops than for single crops in all ecological regions. In the 0-10 cm soil layer, the contents of total nitrogen (TN), microbial biomass nitrogen (MBN), soil organic matter (SOM), soluble organic nitrogen (SON), urease (UE), nitrate reductase (NR), sucrase (SC), and bacterial community alpha diversity, as well as relative abundance of dominant bacteria, were higher for mixed crops than for oats unicast. In addition, soil physical properties, nitrogen fractions, and enzyme activities varied in a wider range in the 0-10 cm soil layer than in the 10-20 cm layer, with larger values in the surface layer than in the subsurface layer. MBN, SON, UE, SC and CAT were significantly and positively correlated with forage yield (P < 0.05). ANN, NN, SOM and cropping systems (R) were significantly and positively correlated with Shannon and bacterial community. The highest yields in the three ecological regions were 13.00 t·ha-1 for YS in MY, 10.59 t·ha-1 for YC in GN, and 10.63 t·ha-1 for YS in HZ. We recommend planting oats and forage peas in the Qilian Mountains Basin, oats and fava beans in the Sanjiangyuan District, and oats and forage peas in Huangshui valley. Our results provide new insights into eco-friendly, sustainable, and cost-effective forage production in the Qinghai Alpine Region in China.